2021
DOI: 10.1038/s41598-021-03125-x
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of the disastrous debris flow of Chediguan gully in Yinxing town, Sichuan Province, on August 20, 2019

Abstract: On August 20, 2019, at 2 a.m., a disastrous debris flow occurred in Chediguan gully in Yinxing town, China. The debris flow destroyed the drainage groove and the bridge at the exit of the gully. In addition, the debris flow temporarily blocked the Minjiang River during the flood peak, flooding the Taipingyi hydropower station 200 m upstream and leaving two plant workers missing. To further understand the activity of the debris flow after the Wenchuan earthquake, the characteristics of this debris flow event we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Large, severely burned areas (Wall et al., 2020), short‐term heavy rainfall (Staley et al., 2020), and steep terrain (N. Li et al., 2021) created favorable conditions for debris flow. The area of moderate and high severity burned area in Xiangjiao catchment has reached 32.6 km 2 , the peak 30‐min rainfall intensity has reached 20.2 mm h −1 , and the mean hillslope angle is 29°.…”
Section: Resultsmentioning
confidence: 99%
“…Large, severely burned areas (Wall et al., 2020), short‐term heavy rainfall (Staley et al., 2020), and steep terrain (N. Li et al., 2021) created favorable conditions for debris flow. The area of moderate and high severity burned area in Xiangjiao catchment has reached 32.6 km 2 , the peak 30‐min rainfall intensity has reached 20.2 mm h −1 , and the mean hillslope angle is 29°.…”
Section: Resultsmentioning
confidence: 99%
“…We analyzed data from a large number (16) of meteorological stations located at high and low elevations to reduce the uncertainties associated with short-term fluctuations on trend analysis results. Rainfall is one of the dominant debris flow triggering agents in mountainous terrains (Iverson et al, 2011;Li et al, 2021). Solid grains typically comprise 50%-70% of the volume of debris flows (Iverson, 1997;Iverson et al, 2011).…”
Section: Variations In Near-surface Air Temperature and Trendsmentioning
confidence: 99%
“…One potential damage stems from the fact that as debris flow evolves downstream, its components change, and volume and inertia increase, resulting in an exceptionally high impact pressure directly exerted on bridges [13,14]. Investigations have revealed that the impact pressure of debris flows is influenced by many factors including front velocity, flow depth, bulk density, liquid volume fractions, solid volume fractions, and the interaction between debris flows and obstructions [15][16][17][18], and both laboratory experiments and in situ tests have been conducted to physically explain and quantify the impact pressure of debris flow on bridge decks, piers foundation, and abutment [10,19,20]. Additionally, numerical simulations have aided vulnerability analysis of bridge structures [21], and hybrid models have been utilized to simulate both horizontal and vertical forces exerted on bridge decks by debris flow [22].…”
Section: Introductionmentioning
confidence: 99%